Design of concrete walls and slabs for wind-borne missile loadings. (1st September 2019) - Terranova, Brian; Whittaker, Andrew; Schwer, Len
Highlights: Resistance of concrete panels to wind-borne missile impact is studied. Impact velocities bound those specified in USNRC, DOE and ANS guidelines and standards. Concrete tensile strength significanly affects panel resistance to impact. Design guidance provided on minimum panel thickness to resist impact by wind-borne missiles. Abstract: Exterior walls and roofs in safety-related nuclear facilities in the United States, including nuclear power plants, must be designed to resist the loadings imposed by missiles (steel pipes, steel spheres, automobiles) borne by hurricanes and tornadoes. For confinement or containment, these walls and roofs are constructed from reinforced and/or prestressed concrete. The minimum required thicknesses of a reinforced panel to prevent scabbing and perforation for an impacting steel pipe are typically established using empirical formulae calibrated for rigid missiles and high velocities. To enable improved design of concrete panels to prevent scabbing and perforation by wind-borne steel pipes, numerical simulations were performed to: (1) investigate the effects of panel thickness, pipe mass and diameter, pipe velocity, and concrete uniaxial compressive and tensile strength on impact resistance, and (2) establish minimum panel thicknesses to prevent scabbing and perforation for the pipes and impact velocities specified in standards of practice. The numerical simulations used axisymmetric SPH models validated using data from tests at Sandia National Laboratory in the 1970s of four reinforced concrete panels impacted by Schedule 40 pipes. The values of panel thickness and concrete compressive strength considered in the parametric study are typical of those in existing nuclear power plant structures in the United States. The Schedule 40 pipe is the missile used for simulations because it is referenced in the United States Nuclear Regulatory Commission (USNRC) Standard Review Plan and the Department of Energy (DOE) Natural Phenomena Hazards Analysis and Design Criteria for DOE Facilities that point to Regulatory Guide (RG) 1.76, RG 1.221, and ANS-2.3. The impact velocities bound the maximum velocities recommended in the USNRC and ANS documents for design against the impact of Schedule 40 pipes. A considerable number of design parameters have a meaningful effect on the impact resistance of reinforced concrete panels but the most important, aside from panel thickness and impact velocity, is tensile strength of concrete. Results of the parametric study enable the writing of guidance on the minimum thickness of reinforced concrete panels to resist 152 mm (6 in), 203 mm (8 in) and 254 mm (10 in) diameter Schedule 40 pipes at impact velocities identified in RG 1.76, RG 1.221 and ANS-2.3. Panel thickness ranging from 305 mm (12 in) to 914 mm (36 in) are required to prevent perforation and scabbing caused by the impact of these Schedule 40 pipes. The required panel thickness decreases with increasing tensile strength.